Tofersen in adults with SOD1-ALS: phase 3 VALOR trial and open-label extension results. Issue 9 (12th August 2022) - Shaw, Pamela; Miller, Timothy; Cudkowicz, Merit; Genge, Angela; Sobue, Gen; Nestorov, Ivan; Graham, Dan- ielle; Fanning, Laura; Fradette, Stephanie; McNeill, Manjit
Abstract : VALOR was a Phase 3, placebo-controlled trial to evaluate the clinical efficacy and safety of tofersen in adults with ALS and a confirmed SOD1 mutation (SOD1-ALS). Participants were randomised 2:1 to tofersen 100 mg (3 doses 2 weeks apart, then 5 doses every 4 weeks) or placebo administered intrathecally. The primary endpoint was change from baseline to Week 28 in the ALS Functional Rating Scale-Revised (ALSFRS-R) total score. Key secondary endpoints included CSF total SOD1 concentration and other clinical outcome measures. Participants could continue in an open-label extension (OLE) upon completion of VALOR. 108 total participants were enrolled (tofersen [n=72], placebo [n=36]). VALOR did not achieve statistical significance on the ALSFRS-R at Week 28, the primary endpoint. Tofersen administration led to robust reductions in CSF total SOD1 protein and plasma neurofilament light chain (NfL) at Week 28 compared to baseline. Trends favoring tofersen were seen across clinical outcome measures of respira- tory function, muscle strength, and quality of life. These effects became more apparent with longer-term follow-up in the OLE, particularly with earlier tofersen initiation. Most adverse events were mild to moderate in severity. Serious neurologic events, including myelitis (2%), were seen in tofersen-treated participants. Study sponsored by Biogen.